Assistance of Scientific Work Writing for Lecturers in LLdikti Environment Region 2 (Muhammadiyah University Bangka Belitung) - Citra Dewi; Heri Kuswoyo; Akhyar Ridho (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2021)
Mentoring is a helping activity that is caused by a reason so that it needs to be accompanied. Lecturers as educators have a role in expanding knowledge through writing, where not all educators have mastered professional writing procedures and how to publish scientific riches that have been written so they need to be accompanied. Scientific writing is the result of research and development, reviews, reviews, studies, or thoughts by individuals or groups that are presented in written form and arranged systematically and based on scientific principles. This activity is intended for lecturers in LLDIKTI area 2 Bangka Belitung. The purpose of holding this activity is as a means to broaden the knowledge, understanding and skills of lecturers in writing scientific papers. Activities are carried out by providing material socialization and practical training. Based on the activities that have been carried out, the participants have a sense of motivation and increase their knowledge in writing scientific papers professionally and participants know how to publish scientific papers that have been written.